The Impact of Social Media Sites on Developing Consistently among Students to Achieve Responsible Behaviour: a Field Study for Students of Northern Border University - Benarous, Djamel; Al-Enezi, Hamood; Louail, Bilal (Zielona Góra: Faculty of Economics and Management Press)
The aim of this study was to determine the influence of social media on students` awareness of responsible behaviour during the COVID-19 pandemic. The field study was carried out with a sample of 726 students from Northern Border University. Data were collected from electronically retrieved questionnaires via various communication channels and analysed using hierarchical linear regression.
Keywords: social media; developing; responsible behaviour; field study; Northern Border University; students; media społecznościowe; rozwój; badania terenowe; studenci